2015
DOI: 10.1139/cjpp-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin ETAreceptor antagonist reverses naloxone-precipitated opioid withdrawal in mice

Abstract: Long-term use of opioids for pain management results in rapid development of tolerance and dependence leading to severe withdrawal symptoms. We have previously demonstrated that endothelin-A (ETA) receptor antagonists potentiate opioid analgesia and eliminate analgesic tolerance. This study was designed to investigate the involvement of central ET mechanisms in opioid withdrawal. The effect of intracerebroventricular administration of ETA receptor antagonist BQ123 on morphine and oxycodone withdrawal was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 58 publications
(65 reference statements)
4
14
1
1
Order By: Relevance
“…Thus, oxycodone demonstrates opiate-like dependence effects across species including mice, rats and rhesus monkeys. The signs and their patterns of direction observed in C57BL/6J mice of the current study are similar to those reported in previous studies with other strains of mice that used oxycodone regimens involving continuous drug delivery (Mori et al, 2013; Raehal and Bohn, 2011) or repeated injections (Bhalla et al, 2015) to induce dependence. The regimen to induce physical dependence in the present study was adapted from a previous study that found physical dependence upon morphine to be induced in mice (Muldoon et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, oxycodone demonstrates opiate-like dependence effects across species including mice, rats and rhesus monkeys. The signs and their patterns of direction observed in C57BL/6J mice of the current study are similar to those reported in previous studies with other strains of mice that used oxycodone regimens involving continuous drug delivery (Mori et al, 2013; Raehal and Bohn, 2011) or repeated injections (Bhalla et al, 2015) to induce dependence. The regimen to induce physical dependence in the present study was adapted from a previous study that found physical dependence upon morphine to be induced in mice (Muldoon et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…For oral consumption, all opioids were diluted in tap water. To induce oxycodone dependence, we employed a repeated injection procedure akin to that described by Bhalla et al (2015) [five once daily intraperitoneal (IP) injections of 5 mg/kg]. Berrettini et al 1994), taking into consideration the higher potency of the three opioids employed herein (Gutstein & Akil 2001) and the potential for bitter taste-aversion (e.g.…”
Section: Drugsmentioning
confidence: 99%
“…Approximately 7-10 days following the end of the oxycodone self-administration phase of the study, mice were injected IP, once a day, for 5 consecutive days with 5 mg/kg oxycodone to render them drug-dependent, as demonstrated in a recent study of Swiss-Webster mice (Bhalla et al 2015). At ∼24 h following the fifth oxycodone injection, all mice were assayed for behavioral signs of hyper-emotionality in a test battery, which consisted of a light/dark shuttle box test, a marble-burying test and a Porsolt forced swim test, in a manner akin to our prior studies of alcohol withdrawal (e.g.…”
Section: Emotional Reactivity During Natural Withdrawal From Repeatedmentioning
confidence: 99%
“…Tolerance to morphine was induced using a 3-day cumulative dosing regimen [26, 27]. Morphine treatment schedule consisted of twice-daily s.c. injections of morphine for three days given at (i) 30 mg/kg (a.m.) and 45 mg/kg (p.m.) on day 1; (ii) 60 mg/kg (a.m.) and 90 mg/kg (p.m.) on day 2; and (iii) 120 mg/kg twice (a.m. and p.m.) on day 3 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Tolerance to oxycodone was induced using a 5-day cumulative dosing regimen [24, 27]. Oxycodone treatment schedule consisted of once-daily injections of 5 mg/kg, s.c. of oxycodone for five days (Fig.…”
Section: Methodsmentioning
confidence: 99%